Trends in Cancer Incidence Rates in Georgia, 1982-2011 - Wonsuk Yoo; Steven Coughlin; James Lillard (Georgia Southern University, 2015)
Background: Although data from the Surveillance, Epidemiology, and End results (SEER)-affiliated cancer registry are accessible to the public, there is a shortage of published research describing cancer incidences for White, Black, and other residents in Georgia. The objective of this research is to provide an overview of the trends in incidence of cancer in Georgia. Methods: Incidence data were obtained from the Surveillance, Epidemiology, and End Results (SEER) 9 program, supported by the National Cancer Institute, spanning the years 1982 to 2011. To assess trends over time, age-adjusted cancer incidence rates relative to the 2000 Standard US population and annual percent changes (APCs) were calculated using SEER*Stat software. Results: In Georgia, cancer incidence rates for women increased from 365.1 per 100,000 in 1982 to 404.2 per 100,000 in 2011, with an overall APC of 0.3% (95% confidence interval: 0.2 to 0.4), but, for men, cancer incidence rates showed a slight decline from 528.0 per 100,000 in 1982 to 513.7 per 100,000 in 2011 (APC of 0.2%, 95% CI: -0.6 to 0.1). For Black, White, and Other (Asian/Pacific Islanders/American Indians) females, there were increases in incidence in this period, with APC values of 0.6, 0.4, and 0.3, respectively. For all males and for Black and White males, there were overall decreases in incidence, with APC values of -0.2. For Other males, however, the APC value was -0.9. Conclusions: In Georgia, increases in cancer incidence rates occurred during 1982-2011 among the female population and within various racial groups in this population, but there was relative stability in incidence rates among the male population, except for Other males.